Atomic bridging modulation of Ir–N, S co-doped MXene for accelerating hydrogen evolution. Issue 18 (6th April 2022) - Lin, Wujun; Lu, Ying-Rui; Peng, Wei; Luo, Min; Chan, Ting-Shan; Tan, Yongwen
Abstract : A novel catalyst consisting of Ir single atoms confined in porous N, S co-doped Ti3 C2 T x is successfully constructed through a gelation-and-pyrolysis method, which shows remarkable catalytic activity towards the HER in acidic and basic electrolytes. Abstract : Two-dimensional Ti3 C2 T x MXenes have attracted significant interest as low-cost supports to anchor single atoms owing to their unique properties. Nevertheless, there is still a lack of systematic investigation on the coordinative interaction between single atoms and functionalized MXene. Herein, we construct a novel catalyst consisting of Ir single atoms confined in porous heteroatom (N, S) co-doped Ti3 C2T x . XAS demonstrates the in situ formation of a new bridging structure of Ir atoms with N and S atoms, which enables good dispersion of Ir atoms among the porous N, S-doped Ti3 C2 T x . The optimal IrSA -2NS-Ti3 C2 T x shows remarkable catalytic activity towards the HER in acidic and basic electrolytes. DFT calculations reveal that the N, S co-doped Ti3 C2 T x support can capture electrons from Ir single atoms, resulting in charge redistribution in the interfacial region of the Ti3 C2 T x support, thereby realizing enhanced HER activity. This work demonstrates a new strategy to modulate the atomic bridging status of the atomically dispersed active sites for improving electrocatalysis.